ECONOMIC AND TECHNICAL ANALYSIS OF POSSIBILITY OF USE SOLID BIOFUEL IN POLAND - Konieczny, Sławomir (Acta Scientiarum Polonorum. Oeconomia, 2002)
There are a lot of advantages of using solid biofuels as a source of energy. So that there is a strong need of its development. There are many social, economic, agricultural and ecological factors that affect development of solid biofuels industry. Using biofuels is a great chance for some local communities and agribusiness. The biofuels’ development can create new employment possibilities and some additional incomes from planting energetistic plants. Using biofuels can also reduce costs of some investments in Poland. A straw as a biofuel source can guarantee the best efficiency and the lowest technological requirements.